Valoración de la producción de anticuerpos en un ensayo de vacunas VLP frente a los serotipos 1 y 4 de la lengua azul - Sánchez-vizcaíno, Jose Manuel; Pérez de Diego, Ana Cristina; Espinosa, Laura (Revista Complutense de Ciencias Veterinarias, 2009)
The main purpose of this study was to evaluate by a competitive ELISA test the VP7 antibodies in response to VLPs vaccines for bluetongue serotypes 1 & 1+4, and after the virus challenge, to assess the humoral immune response produced by these VLPs. The three vaccinated groups showed positive results 35 days after the vaccination. However, in non vaccinated animals antibodies were not detected before day 10 post virus challenge. The presence of antibodies in vaccinated animals implies that VLP Vaccines are able to stimulate a humoral response.
Keywords: VLP; Bluetongue virus; Antibodies; Sheep